Food governance for better access to sustainable diets: A review - del Valle M, Martín; Shields, Kirsteen; Alvarado Vázquez Mellado, Ana Sofía; Boza, Sofía (Frontiers in Sustainable Food Systems, 2022)
‘Governance’, understood as organizational governance, is essential to more sustainable food provisioning systems ensuring sustainable health, heritage, and natural environments. Governance enables regional and local perspectives to be aligned with commitments from national and international organizations. Within the wealth of scholarship on food systems governance, agricultural governance and agency is a rarely interrogated dimension, despite the clear impacts of agricultural decisions on health and environmental outcomes. In this paper we discuss the findings of a scoping review that focuses on the question “How can food governance transform food systems to ensure better access to sustainable diets?”, meaning diet that protect health, cultures, and the natural environment. Our results show that it is first needed to determine the governance level and the expected outcomes. From a national perspective, policy coherence is described as a way in which different public institutions can add to the sustainable diets access goal. From a local perspective, community supported activities and the incorporation of local knowledge are also described as ways that can help achieving an improvement on sustainable diets access. Either from a regional or local perspective, commitment from organizations must be ensured for common objectives being aligned. Also, it is necessary to request more from the agricultural sector role in delivering nutritionally and environmentally appropriate food. Thus, the idea of governing agriculture as a health and environmental activity is an approach that should be considered when designing, implementing, and assessing food systems.